The Story of Josef Lainck: From German Emigrant to Alien Convict and Deported Criminal to Sachsenhausen Concentration Camp Inmate - Grams, Grant W. (Border Crossing, 2020)
Josef Lainck, a German national emigrated to Canada in July 1927. He arrived in Quebec City and travelled west to Edmonton, Alberta where he became a burglar and shot a police officer. Lainck was arrested in November 1927 and deported to Germany in 1938, upon arrival he was arrested and interned in the Sachsenhausen concentration camp until April 1945. This article will examine Lainck’s emigration to Canada, arrest and deportation to Nazi Germany. Lainck’s case is illuminating as it reveals information on deportations from Canada and the Third Reich’s return migration program and how undesirables were treated within Germany. The Third Reich’s return migration plan encouraged returnees to seek their deportations as a method of return. Canadian extradition procedures cared little for the fate of foreign nationals expatriated to the country of their birth regardless of the form of government or the turmoil that plagued the nation. This work will compare Canadian to American deportation rates as an illustration of Canada’s harsh deportation criterion. In this article, the policies and practices of immigration and deportation are discussed within a framework of insecurity as a key driver for human mobility in the first half of the 20th century.